2022
DOI: 10.18502/kls.v0i0.11843
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Roles of Extension Workers on Cyber Extension as Information Media

Abstract: Agriculture has been developing, which attracts more attention from all aspects of the economy. Besides, the industrialization of agriculture is the process of transforming agricultural production towards a comprehensive industrial direction in all aspects such as implementing livestock industry or agricultural mechanization, modernization of farming process, production in the form of modern farming (intensive farming, increasing crops, fertilizing in cultivation, and animal production). Thanks to the applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Nevertheless, many farmers still face difficulties in selling their cattle. Hence, technology is needed to facilitate farmers in marketing and selling their livestock (Guntoro et al, 2022). The threat of disease spread can occur at any time, which can potentially lead to losses.…”
Section: Social Characteristics Of Farmersmentioning
confidence: 99%
“…Nevertheless, many farmers still face difficulties in selling their cattle. Hence, technology is needed to facilitate farmers in marketing and selling their livestock (Guntoro et al, 2022). The threat of disease spread can occur at any time, which can potentially lead to losses.…”
Section: Social Characteristics Of Farmersmentioning
confidence: 99%
“…Guntoro, Qui, and Triatmojo [7] revealed that cyber-extension also has some disadvantages such as its uneven distribution to rural areas. Not every village has cyber extension facilities, so the farmers have to go to other places to access it.…”
Section: Introductionmentioning
confidence: 99%